The effectiveness of community education services in influencing socio-economic issues in the Gravelotte Community - Rabapane, Mpho Victor (My University, 2020)
Community education has driven change in societies for time immemorial. The successes of educational services in influencing socio-economic issues in societies across the globe are captured through empirical studies. There are community education services conducted in the Gravelotte community, but they seem not to address socio-economic needs. The level of illiteracy and joblessness is not abated. The purpose of the study was to investigate the extent to which community education services in the Gravelotte community influences socio-economic issues. Qualitative study approach was employed in the study to investigate the subject. The research paradigm engaged was Interpretive within a case study. I used three methods to collect data which were in-depth individual interviews, document analysis and participant observation. Ten participants were interviewed individually using open-ended interview guides. Minutes, journals and related documents were analysed for data triangulation. I participated and observed public meetings and stakeholders’ gatherings within the area under study. The study was conducted in the small semi-urban area of Gravelotte community in Ba-Phalaborwa municipality with a population of about 500 residents of mixed races. The sampling was done purposively as the participants were requested to respond to a matter relative within the community. The generated data was thematically analysed. I interpreted the data generated from informants to make conclusions on answering the main research question. The study brought forth the following findings. There is no secondary school in the Gravelotte community which is detrimental for socio economic development in the area. Community education programmes offered in Gravelotte have significant successes. Several graduates from the TVET college can find employment and some of them start their businesses. The ABET centre in Gravelotte Primary assists mine workers to earn better salaries. There is evidence of success in the education programmes provided in the Gravelotte community. However, the study discovered that the programmes were offered amidst challenges. Planning, participation and partnership were identified as obstacles to proper implementation of education programmes. The use of common planning to deal with educational goals is most required to enhance the success of educational programmes. There is an increased appreciation by the local community to participate in educational matters. Partnerships are being forged between the local community, the municipality and the mines to address the successful implementation of educational programmes. The study recommends that one primary school in the area be empowered to proceed to include a secondary school or provide education up to grade 9. Additionally, that more research is directed into the gap between provision and demand in the future such that the challenges can be extensively investigated. Likewise, that further researches be encouraged to investigate the ability of TVET colleges to collaborate with local communities with intent to find solutions on educational challenges. In conclusion, the study clearly outlines the effects that education has on the socio-economic issues within the Gravelotte community. There are diverse opinions that support each other in areas that are very important for socio-economic development
Thesis (Ph.D.(Curriculum Studies)) -- University of Limpopo, 2020
Keywords: Community education; Effectiveness; Socio economic issuess; Participation; Programmes; Community education; Socio-economic status; Community-based social services